Keterampilan Guru dalam Intervensi Perilaku Menggosok Gigi Anak Retardasi Mental melalui Pendekatan Behaviour Change Therapy - rohisotul laily; hayatunnufus; yulyana sendia martina; Dwi Septiarini (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Dental health problems are still a challenge in society, including children with mental retardation who have limitations in intellectual, social, behavioral, and motor coordination aspects. This condition impacts low oral hygiene, where around 75% of children are classified as poor. This situation occurs due to the limited ability of children to carry out tooth brushing activities independently and the lack of dental health programs specifically designed for mentally retarded children. Therefore, behavior change therapy can be an alternative strategy to change tooth brushing behavior by meeting the special needs of children with intellectual disabilities through tooth brushing skills taught by teachers at school. The goal is to provide an alternative to changing children's tooth brushing behavior. The method used is Quasi-Experimental Control Group Pretest and Posttest Design. Results The behavior change therapy model as an alternative approach to changing the behavior of children with special disabilities of mentally retarded children has an average expert validation score of 86.67 (very feasible). Teacher skills effectively improve the tooth brushing behavior of children with intellectual disabilities through a behavior change treatment model approach, with a p-value of 0.040 (p <0.05) meaning that the behavior change therapy treatment model for brushing teeth of mentally retarded children is effective in improving the tooth brushing behavior of mentally retarded children through teacher skills.